THE COMPOSITIONS OF PRIMARY CARBONATE MELTS AND THEIR EVOLUTION THROUGH WALLROCK REACTION IN THE MANTLE - Dalton J.A.; Wood B.J. (My University, 1993)
We have experimentally determined the compositions of near-solidus melts from depleted natural lherzolite at pressures greater than 25 kbar. The melts are carbonatitic with low alkali contents and Ca/(Ca + Mg) ratios of 0.72–0.74. Primary carbonate melts from fertile mantle are more sodic with Ca/(Ca + Mg + Fe + Na) of 0.52 and Na/(Na + Ca + Mg + Fe) up to 0.15. The melt compositions are similar to many natural magnesio-carbonatites, but differ substantially from the more abundant calcio-carbonatites.Experimentally we find that calcio-carbonatites are produced by wallrock reaction of primary melts with harzburgite at pressures of < 25 kbar. At 15 kbar we have obtained a Ca/(Ca + Mg + Fe + Na) ratio of up to 0.87 and very low Na contents generated by this process. Values of Ca/(Ca + Mg + Fe + Na) up to 0.95 are possible at lower pressures. Low pressure wallrock reaction of primary carbonate melt with fertile lherzolite produces melts richer in Na2CO3, corresponding to possible parental magmas of natrocarbonatite.Wallrock reaction at low pressures transforms the bulk peridotite composition from that of a harzburgite or lherzolite to wehrlite. Examples of such carbonatite metasomatism are now widely documented. Our experiments show that the calcium content of olivine and the jadeite content of clinopyroxene may be used to constrain the Ca and Na contents respectively of the carbonatite melt responsible for metasomatism.